Effects of Human Connection through Social Drones and Perceived Safety. (16th January 2018) - Kong, Hwayeon; Biocca, Frank; Lee, Taeyang; Park, Kihyuk; Rhee, Jeonghoon
Abstract : This study investigates whether people perceive social drones differently depending on pilot type and perceived safety. A "drone campus tour guide" social drone service was examined to explore these values. This study involves a between-subjects experiment using two drone control types (human-driven and algorithm-driven) and two levels of perceived safety (low and high). The results demonstrate that the drone pilot type changes the service experience when the drone is flying in an unsafe manner. In the group where the drones were flown in an unsafe manner, participants exhibited higher levels of satisfaction with the algorithm-driven drone guide, while both types of drones received the same level of satisfaction when they were flown safely. The results have implications for understanding how expectations influence service evaluations in relation to human connection.